Training on Early Detection of Chronic Energy Deficiency in Pregnancy - Angraini, Dian Isti; Apriliana, Ety; Zuraida, Reni; Saftarina, Fitria (Community Development Journal, 2024)
Chronic Energy Deficiency in pregnancy is a condition where pregnant women suffer from a lack of food that lasts for a long time. Pregnant women with chronic energy deficiency have poor eating behavior, which is influenced by knowledge, perception, beliefs and health education. Health education provided by health workers can increase knowledge and change eating behavior and can be done better if assisted by an expert system. The aim of this activity is to train health workers (doctors, midwives, nutritionists) to carry out early detection of chronic energy deficiency in pregnancy using an expert system, increasing knowledge, attitudes and eating behavior of pregnant women. The method that will be carried out is training using the web-based expert system modelangraini.com for health workers, health education for pregnant women, and increasing knowledge and changing eating behavior of pregnant women. This activity was carried out for 1 day and took place in Faculty of Medicine, University of Lampung on Saturday 30 September 2023 with 45 family doctors, midwives and nutritionists in Bandar Lampung City participating. The results of the evaluation of the implementation of the service showed that there was an increase in participants' understanding by 91.1% to good understanding, 8.9% of participants had a fairly good understanding, and no participants had a poor understanding of the causes, risk factors, impacts, prevention methods, and early detection of chronic energy deficiency in pregnancy with techniques that are fast, easy and can help health workers in providing education and interventions on the eating behavior of pregnant women. This training activity can improve the skills of health workers in an effort to increase knowledge, attitudes and eating behavior of pregnant women so that they can prevent, overcome and help reduce the prevalence of chronic energy deficiency in pregnant women and prevent stunting in toddlers. Keywords: early detection, chronic energy deficiency, training, health workers